VOWELS AND THEIR MODIFICATIONS (FAN, TA’LIM, TEXNOLOGIYA VA ISHLAB CHIQARISH INTEGRATSIYASI ASOSIDA RIVOJLANISH ISTIQBOLLARI, 2024)
This article provides a comprehensive examination of English vowels, focusing on the factors influencing their sounds and the modifications they undergo. Vowels, unlike consonants, are produced without significant restriction of airflow, making them central to the rhythm and intonation of speech. The text categorizes vowels into types—short, long, and diphthongs—and explores modifications such as length variation, tense vs. lax quality, diphthongization, nasalization, schwa sound introduction, and vowel reduction.